A Descriptive Quantitative Study on the Knowledge Level of Adolescents toward HIV/AIDS Transmission at Gotong Royong Junior High School, Tobelo, North Halmahera - Roberto Cabu; Imanuel Dumayudha Goloa (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
AIDS is a symptom that appears because infection is caused by an HIV virus that attacks leukocytes the human immune system decreases, HIV/AIDS in North Halmahera Regency during period from January to September 2019 found 84 cases of HIV/AIDS infected and spread to 17 districts Adolescence of transition from childhood to adulthood between 10-24 years, knowledge possessed by adolescents about HIV/AIDS in the transmission and prevention of HIV/AIDS is low, adolescents think that AIDS is only limited commercial sex workers, drug and needle use, and homosexuals. Those who do not know behavior that will risk of contracting HIV/AIDS trigger them to infected or infected with HIV/AIDS. Research objectives to determine the level of knowledge adolescents about the transmission of HIV/AIDS in Gotong Royong Tobelo Middle School. Methods uses is quantitative research methods research instruments in the form of questionnaires, data were analyzed univariately, sampling technique used is simple random sampling, chosen random. The results of research shows knowledge, good category is 1 respondent, sufficient category 24 respondents, category 37 respondents total of 162 students Gotong Royong Tobelo Middle School education from health.Conclusion: Based the research, Adolescent Knowledge about HIV/AIDS transmission, Gotong Royong Tobelo Middle School students concluded of the students had less knowledge, namely 37 respondents because there still lack of information about HIV/AIDS in Gotong Royong Tobelo Middle School students. still have less knowledge about HIV/AIDS.